Workers' organization and waste collectors: socialist perspectives on an occupation on the margins (Buenos Aires, late 19th century) (Quinto Sol, 2025)
At the end of the 19th century hundreds of laborers worked in cleaning tasks at the Quema (open burning of waste) in the city of Buenos Aires (Argentina); among them, recycling waste collectors, some hired by the concessionaire and others who recovered recyclable waste on their own. The recovered materials were used as industrial raw material and for agricultural uses. Within the framework of the growing “health issue”, different views were cast on this site and these workers, generally condemning and stigmatizing ones. Among those, a different perspective was that of some socialist militants who approached that place concerned about working conditions. This article analyses the testimonies of some important figures of Argentine socialism about the people who were dedicated to the recovery of waste in the burning. In particular, it explores the way in which they conceived the work they were carrying out and how they saw their possible place within the labor movement in formation. In this way, the article takes up the classic question about the formation of the working class, analyzing an occupation that was in a diffuse place between work and no-work.
Keywords: work; waste recycling; socialism; garbage